A population of dust-rich quasars at z ∼ 1.5 - Dai, Y; Bergeron, J; Elvis, M; Omont, A; Huang, J; Bock, J; Cooray, A; Fazio, G; Hatziminaoglou, E; Ibar, E; Magdis, G; Oliver, S; et al. (Institute of Physics Publishing, 2012)
We report Herschel SPIRE (250, 350, and 500 μm) detections of 32 quasars with redshifts 0.5 ≤z < 3.6 from the Herschel Multi-tiered Extragalactic Survey (HerMES). These sources are from a MIPS 24 μm flux-limited sample of 326 quasars in the Lockman Hole Field. The extensive multi-wavelength data available in the field permit construction of the rest-frame spectral energy distributions (SEDs) from ultraviolet to the mid-infrared for all sources, and to the far-infrared (FIR) for the 32 objects. Most quasars with Herschel FIR detections show dust temperatures in the range of 25-60K, with a mean of 34K. The FIR luminosities range from 1011.3 to 1013.5 L, qualifying most of their hosts as ultra- or hyper-luminous infrared galaxies. These FIR-detected quasars may represent a dust-rich population, but with lower redshifts and fainter luminosities than quasars observed at 1mm. However, their FIR properties cannot be predicted from shorter wavelengths (0.3-20 μm, rest frame), and the bolometric luminosities derived using the 5100Å index may be underestimated for these FIR-detected quasars. Regardless of redshift, we observed a decline in the relative strength of FIR luminosities for quasars with higher near-infrared luminosities. © 2012. The American Astronomical Society. All rights reserved.